Towards data-driven urban planning: Developing a real-time data update framework for unfit-for-habitation houses in Jakarta - Prasetyo, Ryan Faza; Sari, Feby Kartika; Rezandi, Fajar; Putra, Adhitya Utama (Community Empowerment, 2025)
Rapid population growth in DKI Jakarta has led to increased territorial density, resulting in a growing number of slums and a housing gap in the availability of decent housing. One of the main challenges in urban planning is the unavailability of accurate and up-to-date data on Unfit-for-Habitation Houses (RTLH), which is still based on sampling methods. Therefore, the primary objective of this community service activity is to develop an efficient data update framework, enabling the Department of Public Housing and Settlement Areas (DPRKP) to update data in real-time without the need for extensive re-surveys. The implementation method involved outreach to the Sub-Department of Public Housing and Settlement Areas (PRKP) across various administrative regions of Jakarta, followed by question-and-answer sessions and discussions. The results indicate that the developed data update framework can enhance the accuracy and efficiency of RTLH information management, thereby supporting more effective data-driven decision-making for the local government.